2012
DOI: 10.1037/a0026938
|View full text |Cite
|
Sign up to set email alerts
|

Competitive versus cooperative exergame play for African American adolescents' executive function skills: Short-term effects in a long-term training intervention.

Abstract: Exergames are videogames that require gross motor activity, thereby combining gaming with physical activity. This study examined the role of competitive versus cooperative exergame play on short-term changes in executive function skills, following a 10-week exergame training intervention. Fifty-four low-income overweight and obese African American adolescents were randomly assigned to a competitive exergame condition, a cooperative exergame condition, or a no-play control group. Youths in the competitive exerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
1
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 40 publications
7
116
1
9
Order By: Relevance
“…29,30 However, in human and animal studies, adiposity has been found to be a source of inflammatory cytokines, which a recent study found mediated cognitive deficits in mice. 31 In addition, exercise and obesity intervention studies in overweight and obese older children have found improvements in motor skills and general cognitive functions with decreases in BMI percentile, 32,33 suggesting a directionality similar to our finding. Further, a nationally representative prospective study found that becoming overweight between kindergarten and third grade was a significant risk factor for adverse academic and behavioral school outcomes in girls.…”
Section: Discussionsupporting
confidence: 77%
“…29,30 However, in human and animal studies, adiposity has been found to be a source of inflammatory cytokines, which a recent study found mediated cognitive deficits in mice. 31 In addition, exercise and obesity intervention studies in overweight and obese older children have found improvements in motor skills and general cognitive functions with decreases in BMI percentile, 32,33 suggesting a directionality similar to our finding. Further, a nationally representative prospective study found that becoming overweight between kindergarten and third grade was a significant risk factor for adverse academic and behavioral school outcomes in girls.…”
Section: Discussionsupporting
confidence: 77%
“…2 estudios realizaron los grupos de manera aleatoria (Flynn et al, 2014;Staiano et al, 2012) y otros 2 no realizaron aleatorización de grupos (Best, 2011;Gao et al, 2016). Presentan un total de 252 sujetos.…”
Section: Figura 1 Flujo De Artículos a Través Del Proceso De Búsquedaunclassified
“…Todos ellos pertenecen al continente americano (USA). Las variables de AF que se controlaron fueron la frecuencia cardiaca (Best, 2011), resistencia y fuerza (Staiano et al, 2012), la puntuación dada por el juego tras la sesión de práctica y el tiempo en recorrer una milla antes y después de la intervención con la Nintendo Wii . Las medidas de rendimiento a nivel cognitivo se centraron en las funciones ejecutivas ¾esfuerzo académico, nivel de logro, frustración, aburrimiento, autoconcepto¾.…”
Section: Figura 1 Flujo De Artículos a Través Del Proceso De Búsquedaunclassified
“…Video game use may beneficially affect visuospatial attention and mental rotation capabilities [78][79][80]. Exergames [81,82] and brain training games may improve executive function [83]. The implications of "brain training" effects on the immature brain are not completely understood [84].…”
Section: Sedentary Behavior and Screen Timementioning
confidence: 99%